Development of phenylboronic acid-functionalized nanoparticles for emodin delivery1. Issue 18 (14th May 2015) - Wang, Bo; Chen, Limin; Sun, Yingjuan; Zhu, Youliang; Sun, Zhaoyan; An, Tiezhu; Li, Yuhua; Lin, Yuan; Fan, Daping; Wang, Qian
<x xml:space="preserve">Abstract</x> The uniform PBA-functionalized nanoparticles were fabricated using the PBA homopolymer via the solvent displacement method. PBA-NPs can be used as a carrier to load polyphenolic drugs.